Little ballerinas - Morris, Ann, 1930-; Sheehan, Nancy (New York : Grosset & Dunlap, 1997)
Photographs and simple text follow some young ballet dancers from preparation for class through a recital.
2.8
K-3
Keywords: Ballet dancing -- Juvenile literature; Ballerinas -- Juvenile literature; Ballet dancing; Ballet dancing